The lived experiences of junior police officers in the Singapore Police Force - Ng, Tiffany Bee Whay (2017)
This study seeks to discover the lived experiences of the junior police officers in Singapore through the qualitative interviews of ten police officers in the Singapore Police Force. The findings revealed the existence of superstitious taboos and its socialisation within the police force as an organisational myth. Although unofficial, these superstitious taboos serve functional value and legitimacy in the organisation. In addition, technology and social media developments have influences on the work of the police. Through the understanding of how these surveillance works and how it affects their job, the paper also helps us to recognise the innate conflict between the occupation’s demand and the community’s interest that locates the police in a contradictory position in the class structure.